Lichen Simplex Chronicus on the Scalp: Broom Fibers on Dermoscopy; Gear Wheel Sign and Hamburger Sign on Histopathology - Agrawal, Sandip (Indian Dermatol Online J, 2020)
Lichen simplex chronicus (LSC) is characterized by lichenification of the skin because of primary excessive scratching. Herein, we present two cases of scalp LSC with a patch showing localized hair loss and paroxysmal severely itching on that area. Dermoscopy examined the presence of broom hair fibers while histopathological examination revealed gear wheel sign, hair shafts split in two (the hamburger sign), and decrease in the size of the sebaceous glands.